Literature as a Medium of Memory: the Holocaust in Contemporary Literature - Marx, Friedhelm (Revista de Filología Alemana, 2011)
of the 20th Century. This symptomatic delay is also to be observed in German literature: in the nineties several novels and autobiographies appear, which tie the Holocaust, each in a specific way, to the Germans’ cultural memory. The article exemplifies different forms of literary memory of the Holocaust with Martin Walser’s A Gushing Fountain, Uwe Timm’s In My Brother’s Shaddow, W.G. Sebald’s Austerlitz and Bernhard Schlink’s The Reader. These works range between autobiographies and novels; a common aspect in all of them is the attempt to address the Holocaust, without smoothening the horrors that are associated with this event. The literature turns out to be a medium of memory, which also reflects the process of memory in a critic way.